The Impact of Virtual Reality Technologies in Digital Media on Audience Experience: An Applied Study on Real Estate Events in The Kingdom of Saudi Arabia During the Year 2025 - Al-Dawsari, Sara Saad; Al-Shuwaikhat, Sadiq Ali Mubarak (Arab Journal for Sciences and Research Publishing, 2025)
This study aimed to evaluate the impact of virtual reality (VR) technologies in digital media on audience experiences at real estate events in Saudi Arabia in 2025 by analyzing user engagement, satisfaction levels, and their influence on real estate decisions. Using a descriptive-analytical approach, the study employed an online survey on a stratified random sample of 250 participants. Findings indicated a high acceptance of VR in digital real estate media, with a mean score of 3.92 and 71.8% of participants agreeing on its effectiveness. The quality of technical infrastructure significantly influenced user satisfaction, explaining 46.8% of its variance. The 26–35 age group exhibited the highest engagement (73.2%), while postgraduate degree holders showed the highest acceptance (77.5%). Path analysis revealed direct and indirect effects of independent variables on dependent ones, with the strongest direct effect from technical quality to satisfaction (path coefficient = 0.534, T-value = 8.976). Key challenges included slow response times (36.8%), technical difficulties (31.2%), and usage costs (18%). Multiple regression analysis highlighted the relative importance of influencing factors, with technical quality having the strongest impact (coefficient = 0.384), followed by ease of use (0.312). Additionally, 38% of participants anticipated VR becoming the primary tool for real estate marketing, while 32.8% saw it as a complement to traditional methods. The study recommended enhancing technical infrastructure, improving the realism of virtual real estate experiences, developing user training programs, and integrating VR with traditional marketing strategies, along with further research in real estate marketing.
Keywords: Virtual Reality Technologies; Digital Media; Digital Real Estate Marketing; User Experience; Virtual Real Estate Events; Digital Media